A educação superior no contexto do PROUNI - Colleoni, Cristini (2012)
This master s dissertation is the result of a study of literature and documents related to widening access to higher education policy in Brazil from 1990, which resulted in the creation of programs for this purpose, especially Prouni University Program for All. This program was created during the government of Luiz Inácio Lula da Silva (2003-2010), 2010), in the context of new requirements for higher education in the training of workers today. It was sought to understand the reasons that permeated the debate over the democratization of access to university, assuming that they express the contradictions inherent from the reality/society in which they operate. This is because, studying the facts of the creation of the university in Brazil, it was found that it was created to train the elite who should rule the country and act in its modernization process. Thus, the democratization of access to university should be controlled as it should be only for the most qualified. Therefore, the origin of the university in Brazil, aimed at a bourgeois project, based on liberalism, to organize a newly independent country. However, during the twentieth century, from the crises of the capitalist mode of production, governments in developing countries, especially Brazil, sought at the university the quickest way to ensure the training of skilled labor to work in the developmental gait. In this sense, there was a concern to broaden access to higher education by the government, but without the need of the state to meet the cost. Apparently, the university received a new function, to train workers. However, the formation of man came to be defined by the logic of the market, without worrying anymore about the scholarly knowledge, nor the formation of intellectual s elite but with the pragmatic knowledge for maintenance and reproduction of the existing order. In order to widen access to university, the governments of the 1990s and first decade of this century, found in the private sector s their greatest ally. Thus, in the government of former President Luiz Inácio Lula da Silva, Prouni was considered the cause of the increase of enrollments in private higher education institutions in Brazil. Therein, analyzing the Prouni, it is intended to understand access policies, the process of social change and the transformation for which the society has been through, since 1990, and the impacts they have caused in the state of Paraná and in the city of Cascavel.